2020
DOI: 10.1093/gerona/glaa139
|View full text |Cite
|
Sign up to set email alerts
|

Dementia is Associated With Poorer Quality of Care and Outcomes After Stroke: An Observational Study

Abstract: Background To determine whether preexisting dementia is associated with poorer quality of care and outcomes after stroke in the acute hospital phase. Method This was a retrospective analysis of pooled data from the Australian Stroke Foundation national audit conducted in 2015 and 2017. Dementia status was obtained from the medical records. Processes of care to assess quality included: stroke unit care, time-dependent therapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 28 publications
2
24
1
Order By: Relevance
“…This is consistent with what has been reported in the literature (10) and may be attributed to survival bias, since women have longer life expectancies than men on average and dementia is typically diagnosed in later years (19,20). A smaller proportion of those with pre-stroke dementia received IV tPA within 4.5 hours, which is consistent with findings from an Australian study (21). The lack of adherence may be due to barriers in patients' ability to describe their symptoms to clinicians, but it is unclear why this barrier did not impact other metrics.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with what has been reported in the literature (10) and may be attributed to survival bias, since women have longer life expectancies than men on average and dementia is typically diagnosed in later years (19,20). A smaller proportion of those with pre-stroke dementia received IV tPA within 4.5 hours, which is consistent with findings from an Australian study (21). The lack of adherence may be due to barriers in patients' ability to describe their symptoms to clinicians, but it is unclear why this barrier did not impact other metrics.…”
Section: Discussionsupporting
confidence: 91%
“…In their initial scoping review of 76 articles, Bunn et al 15 found that in ten of the eleven articles that compared access to treatment between people with and without dementia, people with dementia were less likely to have the same level of access to or quality of care. These findings were replicated in Australia by Callisaya et al 17 While patients with dementia in Australia were thrombolyzed more often within 60 minutes than patients without dementia, patients with dementia were less often admitted to stroke units and less likely to be treated with IVT for ischemic stroke. Being admitted to a stroke unit made it more likely for a patient with dementia to receive rehabilitation and decreased the mortality rate.…”
Section: Differences In Treatment For Patients With Versus Without Di...mentioning
confidence: 73%
“…39 We found evidence that people with disabilities did not receive equitable access to treatment ranging from being admitted to stroke units to receiving post-stroke rehabilitation. 17,27,40 There is no convincing evidence of increased risk of hemorrhage or specific stroke treatment associated complications for people with disabilities, yet disability is often an exclusion criterion in treatment trials; thus, physicians lack high-quality data to guide treatment decisions for their patients who have disabilities/pre-existing impairments. 41,42 Stroke therapies must be developed in consideration of the target population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Aphasia and neglect, frequent after stroke, could complicate cognitive evaluation; therefore, comprehensive cognitive assessment is recommended. 5 Because risk factors for stroke are also risk factors for dementia, 6 any prestroke cognitive dysfunction or dementia (present in 10% of hospitalized stroke patients 7,8 ) must be distinguished from new poststroke impairments.…”
mentioning
confidence: 99%